On the capability to derive mass estimates from high-low satellite-to-satellite tracking data - WEIGELT, Matthias; VAN DAM, Tonie; Tourian, M. J.; Steffen, H.; Baur, O.; Jäggi, A.; Prange, L.; Meyer, U.; Bock, H.; Mayer-Gürr, T.; Zehentner, N.; Sneeuw, N. (2013)
Recently it has been shown that it is possible to derive time-variable gravity signals from high-low satellite-to-satellite tracking (hl-SST) missions (Weigelt et al. 2013, JGR:Solid Earth, doi:10.1002/jgrb.50283). Based on the GPS information only, we will present results derived from the dedicated gravity field missions CHAMP, GRACE and GOCE which allow us to determine mass estimates for various applications. Hydrologically induced mass changes on land cause the strongest mass variations in the gravity field and can be easily identified in the hl-SST data, especially in areas with strong signals such as the Amazon basin. Ice melt in Greenland can be derived from the data and mass estimates compare well to corresponding GRACE estimates. Also, loading time series based on these gravity field solutions agree well with GPS observations for various stations around the globe. We also discuss the limitations of the data, e.g. in detecting signals related to glacial isostatic adjustment or earthquake-induced gravity field changes. Overall, we will demonstrate that the quality of the GPS data is sufficient nowadays and with a proper processing strategy it is possible to derive reasonable mass estimates. As such, this type of observations may allow to bridge a possible gap between GRACE and its successor GRACE Follow-On scheduled for launch in 2017.